An investigation of the relationship between body mass index at the beginning of pregnancy and pregnancy and delivery outcomes - Fatemeh Kianpour; Haleh Ghaem; Zahra Amiri (Shiraz University of Medical Sciences, 2017)
AbstractBackground: Proper weight gain is essential for the mother's health and pregnancy. On the other hand, insufficient weight gain is directly related to a decrease in the growth and preterm birth. The present study aimed to determine the relationship between the mother's Body Mass Index (BMI) and pregnancy and delivery outcomes in mothers referred to Gerash health centers in 2014.Methods: This retrospective, cohort study was conducted on the data from 554 pregnant mothers referred to Gerash health centers to receive pregnancy healthcare from April to November 2014.Results: The mothers' mean age was 25.9±5.4 years and their mean weight gain was 11.6±4.0 kg. In addition, 62.6% and 37.5% of the babies were born through natural delivery and cesarean section, respectively. About 9% of the children were pre-term, while 91% were term and post-term. Besides, 5.4% and 5.1% of the mothers got gestational diabetes and anemia, respectively. The results of logistic regression analysis showed positive relationships between the type of delivery and BMI (OR: 1.10(95% CI: 1.05-1.14)), history of cesarean section (OR: 0.02(95% CI: 0.01-0.07)), and mother's age (OR: 1.06(95% CI: 1.03-1.10)) (p<0.05). Moreover, a positive relationship was found between the gestational weight gain and infant's birth weight (g) (OR: 18.42(95% CI: 8.02 - 28.82)) (p<0.05).Conclusion: According to the finding, it seems that it would be necessary to plan educational and counseling programs before the pregnancy for the mothers. Therefore, the role of health authorities is more important than ever in promoting the general knowledge to reach the proper weight before and during pregnancy.